Synthesis of 4-(5-(2,3-Dimenthoxyphenyl)-3-(4-Methoxyphenyl)-4,5-Dihydro-1H-Pyrazol-1-y1) Benzenesulfonamide as a Promosing Tyrosinase Inhibitor Candidate - Rahayu Rahayu; Noval Herfindo; Nelly Oscifiani; Neni Frimayanti; Adel zamri (Jurnal Riset Kimia, 2022)
In this study, titled compound 5 has been successfully synthesized with 93% yield. The pyrazoline compound was obtained from the cyclocondensation reaction of 4-hydrazinylbenzenesulfonamide 3 with chalcone (E)-3-(2,3-dimethoxyphenyl)-1-(4-methoxyphenyl)prop-2-en-1-one 4 under basic conditions. The molecular structure was confirmed through analysis of FTIR, NMR and HRMS spectroscopic data. Furthermore, its tyrosinase enzyme inhibitory activity was determined through in vitro assay against tyrosinase of Agaricus bisporus. However, the pyrazoline compound 5 showed lower inhibitory activity than the positive control, kojic acid, whereas the IC50 value of the compound 5 is higher than that of kojic acid. The compound 5 IC50 value was 262.15 ÂµM, while kojic acid IC50 value was 88.52 ÂµM.